Pengaruh Waktu dan Daya Microwave pada Metode Microwave Assisted Extraction (MAE)Terhadap Aktivitas Antioksidan dan Pigmen Ekstrak Daun Ubi kayu (Manihot Utilissima Pohl.) - Nadyasari Putri Hidayat, Putu Ayu; Diah Puspawati, Gusti Ayu Kadek; Ari Yusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 1 (2022): Jurnal ITEPA, 2022)
Cassava leave is a plant that is considered an important ingredient in food products because it has bioactive components such as chlorophyll and flavonoids. Extraction time and power are important factors in Microwave Assisted Extraction (MAE) method. This research was conducted to determine the effect of time and power using microwave essisted extraction method on the characteristic of cassava leaf extract and to find the right of time and power in the MAE method to produce the best cassava leaf extract. The research design used was a factorial Completely Randomized Design (CRD) with the first factor, namely microwave power consisting of 3 levels: 100 watts, 180 watts and 300 watts. The second factor the extraction time consisted of 3 levels: 5 minutes, 9 minutes and 13 minutes. The treatment was repeated 2 times to get 18 experimental units. The data obtained were analyzed by the analysis of variance and if the treatment had a significant effect to variable observed, it was continued with Duncan’s Multiple Range Test. The parameters observed in this study were water content, yield, total chlorophyll, total flavonoids, antioxidant activity and IC50 as well as L *, a *, b * values. The results showed that theinteraction of time and microwave power had a significant effect (P<0.05) on, yield, total chlorophyll, total flavonoids, antioxidant activity and IC50 as well as L* and a* values. The extraction time of 13 minutes and power of 300 watts showed the best treatment with water content of 15.72%; yield of 30.16%; total chlorophyll of 4.17 mg / g; total flavonoids were 66.96 mg QE / g; antioxidant activity was 87.27% and L* values was 31.2; a* value was -13.55; b* value was 19.36.